PROGNOSTIC IMPLICATIONS OF VISIT-TO-VISIT BLOOD PRESSURE VARIABILITY IN THE PATIENTS WITH HEART FAILURE. (June 2018) - Lee, J.-.H.; Hwang, K.; Lee, S.; Cho, H.; Lee, H.; Choi, J.; Jeon, E.; Kim, M.; Kim, J.; Chae, S.; Baek, S.; Kang, S.; et al.
Abstract : Objective: The prognostic value of that visit-to-visit blood pressure variability (BPV) has not yet been validated in heart failure (HF) patients. Design and method: We evaluated the patients hospitalized for acute decompensated HF who registered in the Korean Acute Heart Failure (KorAHF) Registry. Of the 5, 627 patients, 900 patients with atrial fibrillation were excluded. The average BP and BPV, as determined by the standard deviation (SD) and coefficient of variation (CV) of systolic and diastolic BP, were recorded at the time of discharge and in outpatient clinic at 3 months, 6 months and 12 months after discharge. The cardiovascular outcome was defined as a composite of death and rehospitalization with aggravated HF. Results: A total of 3, 727 patients (1703 females) were analyzed. Mean age was 67.4 ± 15.3. Average BP was 132.1 ± 31.5/78.1 ± 18.8 mmHg at admission and 115.2 ± 18.2/67.1 ± 11.5 mmHg at discharge. Average BP was 117.0 ± 16.0/68.0 ± 9.3 mmHg and visit-to-visit BPV was 12.6 ± 7.8/8.5 ± 5.2 mmHg by SD and 10.7 ± 6.4/12.6 ± 7.8 % by CV. After a mean follow up duration of 138.3 ± 77.0 days, 250 patients (6.7%) died and 625 patients (16.8%) were rehospitalization with aggravated HF. The patients with clinical event showed significantly lower SBP (114.4 ± 16.8 vs. 117.7 ± 15.7, P < 0.001) and DBP (66.1 ± 9.0 vs. 68.5 ± 9.3, P < 0.001), but systolic BPV (12.4 ± 8.1 vs. 12.6 ± 7.8 by SD, 10.9 ± 6.8 vs. 10.7 ± 6.3 by CV) and diastolic BPV (9.0 ± 5.6 vs. 8.4 ± 5.2 by SD, 13.7 ± 9.2 vs. 12.3 ± 7.3 by CV) were comparable between two groups. In multiple regression analysis, average SBP and DBP was independent predictor of clinical outcomes, but systolic BPV and diastolic BPV did not predict clinical event. In survival analysis, there was also no association between systolic/diastolic BPV and the composite clinical outcomes. Conclusions: In contrast with other clinical entity, these findings suggest that visit-to-visit BPV is not associated with clinical outcomes in heart failure patients.